ABNORMAL STRUKTUR HISTOLOGIS KORTEKS CEREBELLAR TIKUS DENGAN NORMAL FOLIASI AKIBAT IRADIASI SINAR X MASA POSTNATAL - Win Darmanto (The East Java Biological Society, 2005)
Our previous experiment showed that prenatal exposure of rats to X-irradiation on gestation day 21st as the late gestation period causes heterotopic Purkinje cells and abnormal foliation of the cerebellum. However the present study observed the heterotopik of Purkinje cell layer following exposure of the rats to X-irradiation on postnatal day (P) 4, without abnormal foliation of the cerebellum. It also demonstrated the process of re-derangement of Purkinje cells. Rat pups were exposed to 2.5 Gy X-irradiation and the cerebellum was examined histologically and by immunohistochemistry to identify Purkinje cells. At 6 h after exposure, extensive cell death was observed in the external granular layer (EGL) of the cerebellum. By P7 (3 days after exposure), while Purkinje cells with well developed dendrites aligned underneath the EGL in the control cerebellum, Purkinje cells with shorter and abnormally oriented dendrites failed to align and re-deranged in the heterotopic location. On adult, the cerebellum of rats irradiated was observed almost normal folial developed. It is strong support previous study that the critical stage for cerebellar abnormal foliation caused X-irradiation is in the early postnatal period.